Direct real-time neural evidence for task-set inertia - Evans, Lisa H.; Herron, Jane E.; Wilding, Edward L. (SAGE, 2015)
One influential explanation for the costs incurred when switching between tasks is that they reflect interference arising from completing the previous task—known as task set inertia. We report a novel approach for assessing task-set inertia in a memory experiment using event related potentials (ERPs). After a study phase participants completed a test block in which they switched between a memory task (retrieving information from the study phase) and a perceptual task. These tasks alternated every two trials. An ERP index of the retrieval of study information was evident in the memory task. It was also present on the first trial of the perceptual task but was markedly attenuated on the second. Moreover, this task-irrelevant ERP activity was positively correlated with a behavioral cost associated with switching between tasks. This real-time measure of neural activity thus provides direct evidence of task-set inertia, its duration, and the functional role it plays in switch costs.